Implementasi Nilai Pancasila Ke-2 dalam Penggunaan Kecerdasan Buatan pada Platform Kesehatan SatuSehat - Supriyadi, Thomas Bedha Rosario; Ratna Endang Widuatie; Najwan Azhim Muntazhar Anas; Ester Desiana; Victoria Chelsi Surya Bandur; Iib Robiatul Adawiya (JOURNAL SAINS STUDENT RESEARCH, 2025)
The use of Artificial Intelligence (AI) in the SatuSehat health platform is growing and demands the application of ethical principles aligned with humanitarian values. This study aims to analyze the implementation of the value of "Just and Civilized Humanity," as the second principle of Pancasila, in the use of AI in the SatuSehat system. The research method uses a descriptive qualitative approach through analysis of policy documents, literature reviews, and digital observations of the features and privacy policies of the SatuSehat Mobile application. The results show that approximately 85% of AI features support data transparency and service efficiency, while the remaining 15% still face obstacles in terms of equitable access and digital literacy, especially in non-urban areas. These findings indicate that although efforts to implement humanitarian principles are visible, aspects of justice and personal data protection still need to be strengthened so that AI implementation is truly oriented towards human dignity and equality of health services.